The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1007/s00125-001-0763-8
|View full text |Cite
|
Sign up to set email alerts
|

Short-term moderate sodium restriction induces relative hyperfiltration in normotensive normoalbuminuric Type I diabetes mellitus

Abstract: Diabetic nephropathy is one of the most serious complications of diabetes mellitus. Nephropathy develops in approximately 35 % of diabetic patients [1].Preventive measures include good metabolic control and rigorous antihypertensive treatment, preferably by renin-angiotensin system (RAS) blocking agents [2]. Early abnormalities preceding overt nephropathy include microalbuminuria, a rise in blood pressure and an increase in intraglomerular pressure [3,4]. Volume expansion is probably relevant in these processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 38 publications
4
26
0
Order By: Relevance
“…The MRI-derived values for renal blood flow in our control participants are of the same order of magnitude as previously reported using MRI [27] and clearance methods [8]. Clearance studies have suggested increased [28] or normal [26,29] effective renal plasma flow in younger normoalbuminuric type 1 patients with relatively short disease duration. However, our normoalbuminuric patients were older, with much longer durations of diabetes.…”
Section: Discussionsupporting
confidence: 83%
“…The MRI-derived values for renal blood flow in our control participants are of the same order of magnitude as previously reported using MRI [27] and clearance methods [8]. Clearance studies have suggested increased [28] or normal [26,29] effective renal plasma flow in younger normoalbuminuric type 1 patients with relatively short disease duration. However, our normoalbuminuric patients were older, with much longer durations of diabetes.…”
Section: Discussionsupporting
confidence: 83%
“…The preferential effect of SGLT2 inhibition on R A , rather than R E , is important in light of how these agents could potentially be used in patients taking renin-angiotensin-aldosterone system (RAAS) inhibitors [7]. The renal effects of SGLT2 inhibition could be complementary to the well described changes in R E achieved with RAAS blockade, an intriguing concept for the design of future renal protection studies using the combination of dual SGLT2-RAAS inhibition (ACE inhibition or angiotensin II receptor blockade) to normalise glomerular hyperfiltration (ESM Fig.…”
Section: δP Fmentioning
confidence: 99%
“…Of these, 11 were crosssectional studies, [10][11][12][13][14][15][16][17][18][19][20] 5 were longitudinal cohort studies, [21][22][23][24][25] and 20 were intervention trials. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] The weighted means of sodium intake were similar among studies in which consumption was assessed by means of spot urine samples 13,16,17,19 (mean, 156 mmol/d; range, 96-209 mmol/ d) 16,17 and 24-hour urine collections 10,11,14,15,20,22,24,…”
Section: Resultsmentioning
confidence: 99%